Osing Kids and the banners of Blambangan; Ethnolinguistic identity and the regional past as ambient themes in an East Javanese town - Arps, Bernard (UI Scholars Hub, 2009)
On the basis of the theoretical notions of discursive ambience and ambient discourse, this article examines the recent history of language and ethnicity in Banyuwangi in the far east of Java. Over the last three decades (with roots going back to the 1920s and earlier) a redefinition of the language and culture of the